Investigating the role of soil-transmitted helminth infections in the development of leprosy in endemic regions - Singh, Vikram; Turankar, Ravindra P.; Pathak, Vinay Kumar; Singh, Itu; Sharma, Rahul; Goel, Anjana; Sengupta, Utpal (Frontiers in Immunology, 2025)
BackgroundIndia alone contributes nearly 54% of the global load of new cases of leprosy and 21% to global helminthic parasitic infection cases. Research studies have suggested that Soil-transmitted helminth (STH) infection can regulate the host’s immune response and make them susceptible to leprosy. This study aimed to investigate the association between helminth infection and leprosy.Materials & MethodsStool samples (n=360) were collected from 96 patients and 264 household contacts (HHCs) from the endemic region in Purulia (West Bengal) and Champa (Chhattisgarh) India. Samples were examined microscopically for the presence of intestinal helminthic parasites; Cytokine profiling (IFN-γ, IL-12, IL-10) was performed by ELISA on a subset of helminth-positive and negative patients to assess immune responses.ResultsIntestinal parasites were detected in 26% of leprosy patients and 17% of HHCs. Male patients with helminth infection had a significantly higher risk of multibacillary leprosy (OR = 2.60; 95% CI: 1.22–5.55; p = 0.019); no significant association was observed in females or overall, between cases and HHCs. IFN-γ levels were significantly reduced in helminth-positive cases (mean 19.70 pg/ml) compared to helminth-negative cases (mean 46.60 pg/ml; p < 0.02), indicating Th1 suppression. IL-12 and IL-10 levels did not differ significantly between groups. Over five years, 30 HHCs developed leprosy, but no significant association with baseline helminth status was observed (p = 0.816).ConclusionAlthough STH co-infection suppressed Th1 responses in leprosy patients, no direct population-level association with leprosy incidence was established. Integrated parasite control measures may complement leprosy programs by mitigating potential immunomodulatory risks, particularly in high-burden settings.